2010
DOI: 10.1055/s-0030-1247500
|View full text |Cite
|
Sign up to set email alerts
|

DASH-Daten nicht-klinischer versus klinischer Personengruppen – eine Vergleichsstudie mit T-Normen für die klinische Praxis

Abstract: Using T-norms a reference framework has been established for DASH scores, thus making it possible to interpret and compare individual scores between patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
5
2
1
Order By: Relevance
“…Surprisingly, it is not the grinders with their loading and repetitive activity tasks that have the highest (=worst) DASH score, but the packers whose work tasks are defined as repetitive with less loading and more variability in the movement sequences. This finding contrasts with a study which has shown significant differences in DASH scores between manually demanding and manually low-demanding jobs in favour of the latter [48]. One reason for this could be that working hours and job designs have changed significantly in the medical device industry in recent decades so there may be no relevant differences to other occupational groups with a lower workload.…”
Section: Dash and Other Measurement Valuescontrasting
confidence: 73%
See 3 more Smart Citations
“…Surprisingly, it is not the grinders with their loading and repetitive activity tasks that have the highest (=worst) DASH score, but the packers whose work tasks are defined as repetitive with less loading and more variability in the movement sequences. This finding contrasts with a study which has shown significant differences in DASH scores between manually demanding and manually low-demanding jobs in favour of the latter [48]. One reason for this could be that working hours and job designs have changed significantly in the medical device industry in recent decades so there may be no relevant differences to other occupational groups with a lower workload.…”
Section: Dash and Other Measurement Valuescontrasting
confidence: 73%
“…Active range of motion of the wrist and pain on the visual analogue scale (VAS) showed no abnormalities or relevant differences between the groups. The measured values for grip strength were partly below the published reference values, taking into account handedness, age, and sex [38,48]. In the Purdue Pegboard Tests our subjects mostly performed below than the reference values given [40,55].…”
Section: Dash and Other Measurement Valuescontrasting
confidence: 56%
See 2 more Smart Citations
“…Er wurde erkl ä rterma ß en so konzipiert, dass ein Vergleich zwischen pr ä -und postoperativer Befragung m ö glich ist, und erlaubt daher eine vergleichende Bewertung elektiver Eingriff e [1,2] . F ü r alleinige Nachuntersuchungen l ä sst er sich nat ü rlich auch verwenden [6] . Der DASH-Score wird als der f ü r Patienten mit multiplen Funktionsst ö rungen der oberen Extremit ä t am besten geeignete betrachtet [7] .…”
Section: Diskussion ▼unclassified